Leveraging the BRICS Digital Partnership for Collaborative Digital Governance - Odilile Ayodele; Vhonani Petla (Journal of BRICS Studies)
As the global economy becomes increasingly underpinned by the digital economy, developing countries must grapple with the challenge of digitally transforming their economies while ensuring that no one is left behind.  The BRICS countries - Brazil, Russia, India, China, and South Africa - are at different stages of digital development and have adopted varying approaches to digital governance.  However, the challenges of the 21st century require a joint approach to e-commerce, internet governance, and the challenges of a digitalising global economy.  The BRICS Digital Economy Partnership Framework, launched in 2022, is a positive step towards a comprehensive digital governance framework.  This framework promotes cooperation on various digital issues, including cybersecurity, data protection, and e-commerce.  This policy brief examines how the framework can be leveraged to benefit the BRICS countries.